The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.omtn.2021.02.010
|View full text |Cite
|
Sign up to set email alerts
|

miR-204 silencing reduces mitochondrial autophagy and ROS production in a murine AD model via the TRPML1-activated STAT3 pathway

Abstract: Mitochondrial dysfunction is an early feature of Alzheimer's disease (AD), whereby accumulation of damaged mitochondria in conjunction with impaired mitophagy contributes to neurodegeneration. Various non-transcribed microRNAs (miRNAs) are involved in this process. In the present study, we aimed to decipher the participation of miR-204 in a murine AD model. Primary hippocampal neurons were isolated from mice and treated with b-amyloid 1-42 (Ab1-42) to establish a cell model of AD. Dichloro-dihydro-fluorescein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…PINK1 overexpression enhances autophagy signaling by activating autophagy receptors OPTN and NDP52, thereby promoting clearance of damaged mitochondria, reducing oxidative stress, and alleviating synaptic damage and cognitive decline in APP/PS1 mice [ 107 ]. Studies on the role of non-transcribed microRNAs in mitophagy reveal that inhibiting miR-204 expression can efficiently inhibit AD progression by improving mitophagy [ 108 ].…”
Section: The Potential Of Targeting Mitophagy To Treat Admentioning
confidence: 99%
“…PINK1 overexpression enhances autophagy signaling by activating autophagy receptors OPTN and NDP52, thereby promoting clearance of damaged mitochondria, reducing oxidative stress, and alleviating synaptic damage and cognitive decline in APP/PS1 mice [ 107 ]. Studies on the role of non-transcribed microRNAs in mitophagy reveal that inhibiting miR-204 expression can efficiently inhibit AD progression by improving mitophagy [ 108 ].…”
Section: The Potential Of Targeting Mitophagy To Treat Admentioning
confidence: 99%
“…In addition, miR-338 targets to cytochrome-c oxidase subunit 4I1 (COX4I1) to regulate mitochondrial ATP production in brains [ 59 ]. Furthermore, miR-204 is upregulated to target transient receptor potential mucolipin-1 (TRPML1) to damage mitochondrial membrane potential and ATP production in AD, and suppression of miR-204 rescues those mitochondrial damages and reactive oxygen species (ROS) productions through upregulation of TRPML1 [ 60 ]. These results indicate brain-enriched miRNAs, such as miR-137, miR-338 and miR-204, play critical roles to maintain mitochondrial biogenesis and biofunctions during brain development, and unbalance of these miRNA regulations leads to the progression of neuronal diseases (Fig.…”
Section: Micrornamentioning
confidence: 99%
“…The fluorescent images revealed that DHE was localized to the cytoplasm of neurons in the APP/PS1 brain only (Fig. 4a, b), which may represent Aβ-induced mitochondrial ROS [12, 48]. DHE was also frequently found in aggregated microglia in the APP/PS1 brain.…”
Section: Resultsmentioning
confidence: 99%